Linguistic and Pragmatic Study of Word Combinations with Coronamic Elements in Modern Linguistics - To'lanova Sayyoraxon Farxodjon qizi; Usmonova Sanobar Lochinovna (Zien Journals, 2023)
This article provides general concepts of pragmatics, linguistic and pragmatic study of word combinations with coloronymic elements in modern linguistics.
Keywords: Pragmatics; coloronymic cognitive; phraseological